2015
DOI: 10.18410/jebmh/2015/601
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variations of Spleen: A Cadaveric Study

Abstract: ABSTRACT:The Spleen is a large lymphoid organ situated in the left hypochondrial region having an important role in immunological and hematological functions of the human body. The aim of this study was to find the morphological variations of the spleen with respect to it's a) Shape, b) Number of notches on its borders and c) Presence of anomalous fissure on its surface. The Study was done on 60 formalin fixed cadaveric spleen from the Department of Anatomy, Narayana Medical College, Nellore, Andhra Pradesh. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Among the 5 different shapes noted, more commonly were wedge shaped (38%) similar to the studies of Sangeetha et al 6 and Subhash et al, 7 followed by triangular shaped spleens (12%) similar to the study done by R Siva Chidambaram. 5 The average length of spleen in present study was 10.29 cm, which is similar to the studies done by Rao et al 10 (10.5 cm) and Michels et al 11 (11 cm). The average breadth of spleen in present study was 6.37cm, which is similar to the studies done by Sangeethe et al 6 (6.84 cm) and Subhash et al 7 (6.4 cm).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among the 5 different shapes noted, more commonly were wedge shaped (38%) similar to the studies of Sangeetha et al 6 and Subhash et al, 7 followed by triangular shaped spleens (12%) similar to the study done by R Siva Chidambaram. 5 The average length of spleen in present study was 10.29 cm, which is similar to the studies done by Rao et al 10 (10.5 cm) and Michels et al 11 (11 cm). The average breadth of spleen in present study was 6.37cm, which is similar to the studies done by Sangeethe et al 6 (6.84 cm) and Subhash et al 7 (6.4 cm).…”
Section: Discussionsupporting
confidence: 91%
“…9 In these conditions, the clinicians can palpate the splenic notches commonly present on their superior border and differentiate it from other organs. 5 The present study has observed the variations in the morphometry of spleen. The most common shape was the wedge shaped, followed by triangular, tetrahedral, oval and irregular.…”
Section: Discussionmentioning
confidence: 60%
“…The superior border of spleen possess characterstic notch on its anterior part. 9 The knowledgeof anomalous size, shape, notches and other external features may are of importance for surgeons and radiologists.Splenic notches present on superior border are used as a clinical guide to palpate an enlarged spleen.Anomalous splenic notches and fissures can be misinterpreted as splenic injury 10 and splenic lobules are confused as mass originating from left kidney by radiologists. 11 The aim of the study was to find morphological variations of spleen with respect to its number of notches in borders and anomalous fissure on its surfaces.…”
Section: Introductionmentioning
confidence: 99%